Management - Stephen P. Robbins; Mary Coulter (New Jersey Prentice Hall International, Inc., 1996)
This best-selling text demonstrates the real-world applications of management concepts and helps to make management come alive by bringing real managers and students together. It integrates the various disciplines of management and establishes a dialogue with managers from a variety of fields. *The technology package also integrates a book-specific website on PHLIP *Interactive Study guide *Current News Update *Internet Exercises *Opens each chapter with A Manager's Dilemma. These vignettes present real managers and the real situations they face. *Each chapter concludes with Real Managers Respond to Opening Dilemma. Practicing managers provide a short discussion of what they would do if they were faced with the situation described in the chapter opening based on concepts in that chapter. *Ethical dilemma exercises in every chapter are designed to illustrate the dilemmas associated with managing ethically in organizations' i.e., distorting information and firing coworkers.
Keywords: Management